Exploring purchase intentions of new energy vehicles: Do “mianzi” and green peer influence matter? - Zhao, Haibo; Bai, Rubing; Liu, Ran; Wang, Hong (Frontiers in Psychology, 2022)
New energy vehicle is an innovative means of transportation, and its development has been widely concerned all over the world. However, few studies investigate the purchase intention of new energy vehicles (NEVs) from the perspective of combining altruism and cultural factors. Based on the extended norm activation model (NAM), this study explores the influencing factors of new energy vehicles' purchasing intention and the moderating effects of “mianzi” and green peer influence. According to 302 valid questionnaires, the results indicated that the extended NAM model is useful in predicting consumer purchasing behavior with an improved explanatory power in purchase intentions of new energy vehicles from 15% to 26%. The awareness of consequences, ascription of responsibility and green self-identity have a positive impact on the personal norm. Personal norm and green self-identity are positively associated with purchase intention. “Mianzi” and green peer influence positively moderate the relationship between green self-identity and intention to purchase. The ﬁndings give new insights into the impact of cultural factors on purchasing new energy vehicles and profound suggestions for policy makers and enterprises to promote the development of new energy vehicles.